E-Service in University Research - Nasution, Nurliana; Yandra, Alexsander; Arief Hasan, Mhd (International Journal of Engineering and Technology, 2018)
The advancement of information technology plays important role in running an organizationâ€™s business. E-service is a kind of business process as a result of the information technology advancement. A Research Institute and community service (LPPM) in a university keeps its role to manage all the activities of academic in which providing an excellent services for the lecturers as university researchers. An effective and efficient application for providing an excellent service is needed to facilitate the activities of research and community service conducted by lecturers. E-service provides a relationship between organizer service and community as the users mediated by information technology. E-service is a form of software design using internet to facilitate the interactions of clients (people or other forms of electronic services).Â Â